Pengembangan Massive Open Online Cours (MOOC) untuk Mendukung pembelajaran Muatan Lokal Bahasa Sasak - Taufiqqurrahman, Taufiqqurrahman (JUPE : Jurnal Pendidikan Mandala, 2023)
The Language Development and Guidance Agency of the Ministry of Education and Culture has mapped and verified 652 regional languages in Indonesia, the many regional languages owned by the Indonesian people are inseparable from the influence of the Indonesian nation as a archipelago spread from Sabang to Marauke. The number of regional languages that we have is also a big challenge how all cultural assets owned today can be maintained. Talking about maintenance is certainly closely related to what patterns and strategies are most effective to use so that the maintenance target can be obtained.  West Nusa Tenggara Province through Regional Regulation No. 16 of 2021 concerning the promotion of culture also pays special attention to regional languages. The design of this development research will use the Borg & Gall model (2003) and to get a feasible design this research will later conduct trials involving linguists, material experts and learning technology experts.